Pandemic effects on public service employment in Australia. (March 2022) - Colley, Linda; Woods, Shelley; Head, Brian
The COVID-19 pandemic is sending shockwaves through communities and economies, and public servants have risen to the novel policy challenges in uncharted waters. This crisis comes on top of considerable turmoil for public services in recent decades, with public management reforms followed by the global financial crisis (GFC) leading to considerable change to public sector employment relations and a deprivileging of public servants. The research adopts the lens of the 'public service bargain' to examine the effects of the pandemic across Australian public services. How did Australian public service jurisdictions approach public employment in 2020, across senior and other cohorts of employees? How did this pandemic response compare to each jurisdictions' response to the GFC a decade earlier? The research also reflects more broadly of the impact on public sector employment relations and to what extent pandemic responses have altered concepts of the diminished public service bargain or the notion of governments as model employers? JEL Codes: J45